2019
DOI: 10.1080/15389588.2019.1581926
|View full text |Cite
|
Sign up to set email alerts
|

Frontal crash simulations using parametric human models representing a diverse population

Abstract: Objective: Analyses of crash data have shown that older, obese, and/or female occupants have a higher risk of injury in frontal crashes compared to the rest of the population. The objective of this study was to use parametric finite element (FE) human models to assess the increased injury risks and identify safety concerns for these vulnerable populations. Methods: We sampled 100 occupants based on age, sex, stature, and body mass index (BMI) to span a wide range of the U.S. adult population. The target anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Future work will be done to develop an appropriate model morphing technique to match the M50-P and PMHS internal anatomies, which is necessary to improve model subject specific predictions. 65,66 Lastly, the friction coefficient between the test vehicle and body suit that housed the PMHS’s was not reported, leading to us using coefficients found in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will be done to develop an appropriate model morphing technique to match the M50-P and PMHS internal anatomies, which is necessary to improve model subject specific predictions. 65,66 Lastly, the friction coefficient between the test vehicle and body suit that housed the PMHS’s was not reported, leading to us using coefficients found in literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the utility of the model is not simply a matter of biofidelity or limited sizes but also the representation of different injury mechanisms and kinematics, which may have substantial impact on occupant protection. For example, recent studies have shown that occupants with different sizes, shapes, ages, and genders sustained very different kinematics and injury concerns in frontal crashes (Hu et al 2019). The utility of the model is also a matter of the model's sensitivity to changes in restraint design, and this type of sensitivity is rarely assessed for dummies or human body models.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is probabilistic rib fracture risk prediction, which can produce multiple age-adjusted risk predictions from the same, fixed, HBM rib strain predictions. In recent years, morphing (re-shaping) the geometry of HBMs based on statistical human shape models has been used to create several HBMs that geometrically represent male and female occupants of varying age, height, and weight ( Hu et al, 2019 ; von Kleeck et al, 2022 ; Larsson et al, 2022b ). However, these HBMs still represent geometrically average individuals, with an average ribcage shape, for the subpopulation described by each choice of sex, age, height, and weight.…”
Section: Introductionmentioning
confidence: 99%